Composite Resin Coating for The Protection of Surfaces and Metals - Al Pana, Huda; Fakry, Nadia; Hussain, Nessrain (Iraqi Journal of Science, 2023)
The curing process of epoxy resin was investigated with some additives and fillers such as nano fumed silica with primary particle diameter of 56–58 nanometers, fine ferric oxide with an average particle diameter of 0.4 micrometer, fine calcium carbonate with an average particle diameter of 0.58 micrometer, and plasticizer, a new composite resin has been obtained. Based on present experimental results, the new composite resin shows high impact strength and hardness as well as the ability of the composite withstand to degradation from water way in. Additionally, curing time of composite was reduced to the minimum set time than epoxy resin at different temperature. This new composite resin was used appropriately for coating to protect surfaces and metals in marine ships from corrosion which meet the requirements for certain applications such vehicles body, crude oil tankers, petroleum pipelines services, and other applications.